Ecology - Stanley I Dodson...[et al.] (Oxford Univ. Press, 1998)
The book concentrates on the ideas and techniques that separate different concept-based approaches to the study of ecology. It discusses six kinds of ecology: landscape, physiological ecosystem, population, community, anf behavioral, focusing on the kinds of questions ecologists ask about their world rather than on accumulated ecological knowledge.